2014
DOI: 10.1136/bmjopen-2014-005340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of childcare practices on nutritional status of Ghanaian children: a regression analysis of the Ghana Demographic and Health Surveys

Abstract: ObjectivesGuided by the UNICEF framework for childcare, this study examined the association of childcare practices (CCP) with infant and young children's growth (height-for-age Z-scores, HAZ), and investigated whether care practices are more important to growth in some sociodemographic subgroups of children.DesignCross-sectional survey.SettingUrban and rural Ghana.ParticipantsThe study sample comprised 1187 dyads of mothers aged 15–49 years and their youngest child (aged 6–36 months).ResultsThe results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 15 publications
(20 reference statements)
4
58
0
Order By: Relevance
“…A small literature has explored various ways to approach the development of NC indexes, either through care-domain-specific indexes (Armar-Klemesu, Ruel, Maxwell, Levin, & Morris, 2000;Garg & Chadha, 2009) or more complex indexes combining care domains (Amugsi, Mittelmark, Lartey, Matanda, & Urke, 2014;Nti & Lartey, 2008;Osorio, Bolancé, & Alca iz, 2013;Osorio, Bolancé, & Madise, 2015;Ruel et al, 1999). Armar-Klemesu et al (2000), Amugsi et al (2014), Nti and Lartey (2008), and Ruel et al (1999) all used one or more care indexes in their studies of determinants of childcare (Armar-Klemesu et al, 2000;Peter & Kumar, 2014), or care as a determinant of child nutrition (Amugsi et al, 2014;Moursi et al, 2008;Nti & Lartey, 2008;Ruel et al, 1999). Armar-Klemesu et al (2000) constructed separate feeding, preventive health seeking, and hygiene practice indexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small literature has explored various ways to approach the development of NC indexes, either through care-domain-specific indexes (Armar-Klemesu, Ruel, Maxwell, Levin, & Morris, 2000;Garg & Chadha, 2009) or more complex indexes combining care domains (Amugsi, Mittelmark, Lartey, Matanda, & Urke, 2014;Nti & Lartey, 2008;Osorio, Bolancé, & Alca iz, 2013;Osorio, Bolancé, & Madise, 2015;Ruel et al, 1999). Armar-Klemesu et al (2000), Amugsi et al (2014), Nti and Lartey (2008), and Ruel et al (1999) all used one or more care indexes in their studies of determinants of childcare (Armar-Klemesu et al, 2000;Peter & Kumar, 2014), or care as a determinant of child nutrition (Amugsi et al, 2014;Moursi et al, 2008;Nti & Lartey, 2008;Ruel et al, 1999). Armar-Klemesu et al (2000) constructed separate feeding, preventive health seeking, and hygiene practice indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Armar-Klemesu et al (2000) constructed separate feeding, preventive health seeking, and hygiene practice indexes. Amugsi et al (2014) and Ruel et al (1999) combined diet and prevention service use into one childcare index, and Nti and Lartey (2008) included in one index a wide range of care practices, comprising household and personal hygiene, immunization status, dietary diversity, caregiver responsiveness, and hygiene practices during feeding. Engle et al (2000) further advanced childcare measurement by including the role of socioemotional care as a key component.…”
Section: Introductionmentioning
confidence: 99%
“…We estimate this model on a particularly unique population -namely children in households with pregnant women or women with infants. Our data allows us to draw on a rich number of indicators to estimate this frameworkunlike previous work in Ghana, which relied on GLSS or DHS data, lacking many key indicators (Alderman, 1990, Amugsi et al, 2014, Van de Poel et al, 2007, or on a relatively small amount of data (Nti andLartey, 2008, Ruel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Amugsi et al (2015) among other findings revealed older children to have a higher risk of getting cough and diarrhoea relative to younger children in Ghana. Amugsi, Mittelmark, Lartey, Matanda, and Urke (2014) revealed that maternal weight, the number of children less than five years, place of residence and wealth index, child's age and mother's age to be immensely linked with height-for-age Z-scores (Children's Growth) in Ghana. Borbor, Kumi-Kyereme, Yendaw and Adu-Opong (2014) revealed that, younger children, children from poor households, with higher household size, with lesser paternal and maternal education, with younger mothers and from a rural area were more likely to have anaemia.…”
Section: Literature Reviewmentioning
confidence: 99%